STAT3 Inhibition by Centipede Scolopendra Extract in Liver Cancer HepG2 Cells and Orthotopic Mouse Models of Hepatocellular Carcinoma - Teng Yong-Jiea; Liu Zhuob; Liao Liuc; Chen Yuanc; Huang Xiao-Did; Tian Xue-Feic (KeAi Communications Co., Ltd., 2020)
Objective: To observe the effects of Centipede Scolopendra extraction (CSE) on human liver cancer HepG2 cells and the nude mouse tumor model of liver orthotopic transplantation, and to explore the anti-liver cancer mechanism of the extract. Methods: HepG2 cells were respectively treated with CSE250 (250 μg/mL), CSE500 (500 μg/mL) and 5-FU, and control group was established. An enzymatic hydrolysis and acetone precipitation method was used to separate and purify CSE, which was then used to treat HepG2 cells. The CCK8 assay was used to detect the inhibition of cell proliferation and the half maximal inhibitory concentration (IC50) was calculated. Flow cytometry was used to analyze the cell cycle, and western blot was used to detect the expression of signal transduction and activator of transcription 3 (STAT3) pathway-related proteins in HepG2 cells treated with CSE. A nude mouse model with an orthotopic liver tumor was prepared. The mice were randomly divided into four groups, each containing 12 animals: the model group, the 5-FU group, the CSE10 group [10 mg/(kg·d)] and the CSE50 group [50 mg/(kg·d)]. The volume and mass changes in the nude mice with orthotopic transplanted tumors were observed. Western blot method was used to test the protein expression levels of p-STAT3 and p38 mitogen-activated protein kinase (p38MAPK). Tissues from the liver of mice in the model group and the CSE50 group were analyzed by using a protein tyrosine kinase (PTK) chip, and the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) function enrichment analysis of the differentially expressed proteins was performed. Results: This study showed that CSE significantly inhibited the proliferation of HepG2 cells (P < 0.05). After 48 h of CSE treatment, the cell cycle of HepG2 cells manifested as S phase and G2/M phase; p-STAT3 protein levels in the CSE groups were significantly lower than that in the control group (P < 0.05). Analysis of the tumor inhibition in the mice showed that the tumor masses and volume in CSE groups were lower (P < 0.05). The protein levels of p-STAT3 and p38MAPK in CSE50 group and 5-FU group decreased significantly (P < 0.05). PTK antibody chip screening results showed that CSE groups had a bidirectional regulation trend, and there were 23 up-regulated PTKs and six down-regulated PTKs. The GO and KEGG analyses showed that CSE exerted its anticancer effects through regulation of biological processes, including mitogen-activated protein kinase (MAPK) cascade, chemotaxis, cell invasion, cell adhesion, angiogenesis and other biological processes, and through signaling pathways, including the MAPK, phosphatidylinositol-3-kinase/serine threonine protein kinase (PI3K/AKT), and RAS signaling pathways. Conclusions: CSE can effectively inhibite the proliferation of HepG2 cells and effectively inhibite the growth of liver cancer orthotopic transplantation tumor. Its mechanism may be closely related to the regulation of STAT3, MAPK and PI3K/AKT signaling pathways.